“Before I was like a Tarzan. But now, I take a pause”: mixed methods feasibility study of the Naungan Kasih parenting program to prevent violence against children in Malaysia - J. M. Lachman; R. Juhari; F. Stuer; P. Zinser; Q. Han; F. Gardner; A. McCoy; S. N. Yaacob; R. Kahar; M. Mansor; Z. Madon; Z. Arshat; et al. (Springer Nature, 2023)
Background Despite impressive strides in health, social protection, and education, children continue to experience high rates of child maltreatment in Malaysia. This mixed-methods study assessed the feasibility of a fve-session, social learning-based parenting program delivered by government staf in a community setting to reduce violence against children. Methods Parents of children from birth to 17 years were recruited from two communities near Kuala Lumpur to participate in the government-run program called the Naungan Kasih Positive Parenting Program (“Protecting through Love” in Bahasa Melayu). Quantitative data from female caregivers (N=74) and children ages 10–17 (N=26) were collected along with qualitative interviews and focus groups with parents, children, and facilitators. The primary outcome was child maltreatment with secondary outcomes including neglect, positive parenting, acceptability of corporal punishment, harsh parenting, positive discipline, and child behavior problems. Multilevel Poisson regression and multilevel linear regression were conducted to compare baseline and post-test outcomes. Qualitative interviews and focus groups examined how participants experienced the program utilizing a thematic analysis approach. Results Quantitative analyses found pre-post reductions in overall child maltreatment, physical abuse, emotional abuse, attitudes supporting corporal punishment, parent sense of inefcacy, and child behavior problems. There were no reported changes on positive and harsh parenting, parental mental health, and marital satisfaction, nor were there any other signifcant changes reported by children. Qualitative fndings suggested that the program had tangible benefts for female caregivers involved in the program, with the benefts extending to their family members. Conclusions This feasibility study is one of the few studies in Southeast Asia that examined the feasibility and initial program impact of a parenting program delivered by government staf to families with children across the developmental spectrum from birth to 17 years. Promising results suggest that the program may reduce child maltreatment across a range of child ages. Findings also indicate areas for program improvement prior to further delivery and testing, including additional training and content on sexual and reproductive health, parenting children with disabilities, and online child protection.